Burden of early neonatal mortality in Sub-Saharan Africa. A systematic review and meta-analysis. - Natnael Moges; Anteneh Mengist Dessie; Denekew Tenaw Anley; Melkamu Aderajew Zemene; Natnael Atnafu Gebeyehu; Getachew Asmare Adella; Gizachew Ambaw Kassie; Misganaw Asmamaw Mengstie; Mohammed Abdu Seid; Endeshaw Chekol Abebe; Molalegn Mesele Gesese; Yenealem Solomon Kebede; et al. (PLoS ONE)
Background Globally, with a neonatal mortality rate of 27/1000 live births, Sub-Saharan Africa has the highest rate in the world and is responsible for 43% of all infant fatalities. In the first week of life, almost three-fourths of neonatal deaths occur and about one million babies died on their first day of life. Previous studies lack conclusive evidence regarding the overall estimate of early neonatal mortality in Sub-Saharan Africa. Therefore, this review aimed to pool findings reported in the literature on magnitude of early neonatal mortality in Sub-Saharan Africa. Methods This review's output is the aggregate of magnitude of early neonatal mortality in sub-Saharan Africa. Up until June 8, 2023, we performed a comprehensive search of the databases PubMed/Medline, PubMed Central, Hinary, Google, Cochrane Library, African Journals Online, Web of Science, and Google Scholar. The studies were evaluated using the JBI appraisal check list. STATA 17 was employed for the analysis. Measures of study heterogeneity and publication bias were conducted using the I2 test and the Eggers and Beggs tests, respectively. The Der Simonian and Laird random-effect model was used to calculate the combined magnitude of early neonatal mortality. Besides, subgroup analysis, sensitivity analysis, and meta regression were carried out to identify the source of heterogeneity. Results Fourteen studies were included from a total of 311 articles identified by the search with a total of 278,173 participants. The pooled magnitude of early neonatal mortality in sub-Saharan Africa was 80.3 (95% CI 66 to 94.6) per 1000 livebirths. Ethiopia had the highest pooled estimate of early neonatal mortality rate, at 20.1%, and Cameroon had the lowest rate, at 0.5%. Among the included studies, both the Cochrane Q test statistic (χ2 = 6432.46, P <0.001) and I2 test statistic (I2 = 99.80%, p <0.001) revealed statistically significant heterogeneity. Egger's weighted regression (p <0.001) and funnel plot show evidence of publication bias in this meta-analysis. Conclusion This review demonstrated that the pooled magnitude of early neonatal mortality in sub-Saharan Africa is substantial. Therefore, governmental and nongovernmental agencies, international organizations, healthcare providers and institutions and academic and research institutions should give a due attention and design strategies to reduce early neonatal mortality in Sub-Saharan Africa.